Post-operative short-term clinical evaluation of direct lateral (Harding) approach in primary total hip replacement - Abdullah Abdulkareem Abbas; Ahmed Latteef Al-Shamari (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate patients’ functional outcomes after total hip arthroplasty through a direct lateral approach. Methods: The prospective, observational, descriptive study was conducted at Al-Yarmouk Teaching Hospital, Baghdad, Iraq, from May 2019 to June 2020, and comprised patients aged 28-81 years having advanced osteoarthritis and avascular necrosis who underwent cementless total hip arthroplasty. The patients were followed up for 6 months. Outcome was assessed using the Harris hip score, Trendelenburg sign, post-operative hip dislocation, post-operative infection, and heterotopic ossifications. Data was analysed using Excel version 2019. Results: Of the 30 patients, 14(47%) were males and 16(53%) were females. The overall mean age was 49.8±15.28 years. The mean pre-operative Harris hip score was 43.166±8.27, while it was 83.566±3.83 post-operatively (p<0.001). There was 1(3.33%) case of heterotopic ossification, 3(10%) had Trendelenburg sign. There was no case of postoperative hip dislocation or infection. Conclusion: The lateral hip approach was found to be associated with good post-operative hip stability and good post-operative functional outcome with low post-operative risk of infection. Key Words: Arthroplasty, Replacement, Hip, Osteoarthritis, Ossification, Heterotopic, Necrosis